To men and women of Britain : proclamation (leaflet) (1937)
018a-0059-001 To Men and Women of Britain PROCLAMATION FOR eighteen months Spain has been torn by War. Spanish Democracy has been fighting for its very existence against the armed attacks of Franco and his foreign Fascist Allies. Now, when Franco is preparing his German and Italian troops for a yet greater onslaught — now, when the lives of the Spanish people depend on supplies of food and arms — now, when all the world knows that Non-Intervention is a lie in the mouths of the Fascists — is the time for all who wish to preserve Freedom and to protect Peace to rally to the support of the heroic defenders of Spanish Democracy. OUR PEACE IS AT STAKE Unchecked war has spread from Abyssinia to Spain, from Spain to China. Unchecked the Fascist Powers will engulf the world in war. To save the babies of London from gas we must now save the children of Madrid. LABOUR DEMANDS unconditional freedom for the Spanish Government to buy arms and food. LABOUR DEMANDS the immediate withdrawal of foreign armies from Spain. LABOUR OPPOSES any concession to Franco by the National Government of belligerent rights to search and sink ships on the high seas. LABOUR OPPOSES any concession to Franco by the National Government in international law and status. He is a rebel. His troops are invaders. His ships are pirates. SAVE SPAIN - SAVE BRITAIN Leaflet No. 66 (12/37/250). Price 3s 6d. per 1,000 carriage paid from the Labour Publications Department, Transport House, Smith Square, London, S.W.1. Printed by the Victoria House Ptg. Co. Ltd. (T.U. all Depts.), 55 and 57 Drury Lane, W.C.2 292/946/18a/61(i)